Investigating neighbourhood environmental risk factors associated with childhood acute respiratory infection symptoms in Ethiopia mixed effect and multilevel logistic regression analysis based on EDHS 2016 - Azanaw, Jember; Weldegebriel, Fasika; Malede, Asmamaw (Frontiers in Public Health, 2024)
Background Acute respiratory infection is an infectious illness caused by acute viral or bacterial infection. According to a 2018 WHO report, exposures to indoor and ambient air environmental pollution were contributing factors to a higher risk of respiratory problems following 7 million deaths of children under five globally. Housing conditions such as wall material, roof type, kitchen location, sanitation condition, and cooking fuel type are household-level predictors of acute respiratory disease among children under five years of age. Method This research used EDHS-2016 secondary data, which are nationally representative. The data collection period was from January 18, 2016, to June 27, 2016. Among the 16,650 total surveys, 10,006 households that had children below 5 years of age. The outcome variable for this study was acute respiratory infection symptoms. Analyses were performed using STATA Version 17.1. The data were weighted before performing analysis to reinstate the representativeness of the sample. In the bivariable analysis, a p value <0.2 was used to screen for multivariable. Multicollinearity was checked using the variance inflation factor. Then, a multilevel multivariable regression model was used in this study for the analysis of acute respiratory infection symptoms and possible predictor variables. Variables with a p value <0.05 in multivariable regression analysis were considered statistically significant predictors. Results Most (95.00%) households commonly used solid fuel for cooking, and household main construction materials: 81.44 and 91.03% of floors and walls of households were constructed with unprocessed natural materials, respectively. The prevalence of acute respiratory infection symptoms among children under five years of age was 7.955% (7.397, 8.551%). The findings indicated that acute respiratory infection symptoms among children under five years of age were significantly linked with the age of the children, diarrhea status, residence, region, fuel type, stool disposal, wall material, and floor material. Conclusion Interventions should target modifiable factors such as proper stool disposal of the youngest child, informing the health effects of poor housing conditions such as improving wall and floor construction material to reduce acute respiratory infection symptoms among children under five years of age.